1991
DOI: 10.1039/ft9918700897
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of hydroxyl groups in crystalline silicoaluminophosphate SAPO-34 by diffuse reflectance infrared spectroscopy

Abstract: Hydroxyl groups in crystalline silicoaluminophosphate SAPO-34 have been investigated by diffuse reflectance IR spectroscopy. By carefully comparing the intensities of stretching vibrations with the appropriate combination and overtone bands the two types of bridged Si-OH-AI group were assigned to the fundamental stretching vibrations at 3625 and 3600 cm-'. Both types of group exhibited approximately the same acidic properties but differed in their localization. The bridged groups with v = 3600 cm-' were assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 2 publications
1
38
0
Order By: Relevance
“…In the literature there are two ways for labeling the oxygen atoms within the chabazite topology. [50,51] We use the labeling applied in references [52][53][54][55] as illustrated in Figure 1. Three sites are part of an eight-membered ring connecting two cages, whereas the fourth oxygen atom, O(3), is attached to a six-membered ring and is only in contact with one cage.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature there are two ways for labeling the oxygen atoms within the chabazite topology. [50,51] We use the labeling applied in references [52][53][54][55] as illustrated in Figure 1. Three sites are part of an eight-membered ring connecting two cages, whereas the fourth oxygen atom, O(3), is attached to a six-membered ring and is only in contact with one cage.…”
Section: Resultsmentioning
confidence: 99%
“…Two peaks at 3625 and 3598 cm À1 can be attributed to two types of Si(OH)Al groups differed in their localization. The bridged group with y = 3598 cm À1 is assumed to be localized in the hexagonal prism, forming an H-bond with adjacent oxygen atoms of the framework while the isolated bridged OH groups pointing towards the center of the elliptical cages give the vibration frequency at 3625 cm À1 [15][16][17][18]. These two types of OH groups have been considered to have similar acidic properties and to be the active sites for acid-catalyzing reaction [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…If we assigned the former peak to acid sites, the total acid sites calculated from our NH 3 -TPD data were 1.6 and 0.9 mmol/g for SAPO-34_H and SAPO-34_L, respectively, which are comparable to those obtained by 1 H MAS NMR. Studies on the basis of IR experiments [15][16][17][18] showed two distinct Brønsted acid sites. In Refs.…”
Section: H Mas Nmrmentioning
confidence: 99%
“…In Refs. [15,16], the high-frequency component of the OH stretching peaks was assumed to come from bridged OH groups in the hexagonal prism, forming an H-bond with adjacent oxygen atoms of the framework, and the low-frequency component was from isolated bridging OH groups pointing toward the center of the elliptical cage. However, in Ref.…”
Section: H Mas Nmrmentioning
confidence: 99%
See 1 more Smart Citation